2014
DOI: 10.3109/14647273.2014.907506
|View full text |Cite
|
Sign up to set email alerts
|

SPACA3gene variants in a New Zealand cohort of infertile and fertile couples

Abstract: School of Veterinary Medicine and Science, Sutton Bonington Campus, University of Nottingham, Loughborough, UKAbstract SPRASA (also referred to as SLLP1) is a protein identifi ed in the acrosome of human sperm and encoded by the gene SPACA3 . SPRASA is associated with sperm-oocyte recognition and binding, and may play a role in fertility. In order to determine whether variants in the SPACA3 gene are associated with human infertility, we undertook a genetic analysis of 102 infertile and 104 fertile couples. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…As a member of c-type lysozyme/alpha-lactalbumin family, SPRASA has an exon-intron organization and sequence conservation, similar to c-type lysozymes ( Chiu et al, 2004 ; Wagner et al, 2015 ). Afterwards, it has been reported that the protein could be a target for anti-sperm antibodies in some infertile male, playing possible roles in sperm-egg bonding process, as well as subsequent development of early embryo in hamster, murine or bovine models ( Prendergast et al, 2014 ). In this study, the expression of SPRASA was higher in cryopreserved goat spermatozoa without antioxidant cryo-protection, suggesting that this protein may be a potential infertile marker of frozen-thawed goat sperm, and its specific molecular function is worth further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of c-type lysozyme/alpha-lactalbumin family, SPRASA has an exon-intron organization and sequence conservation, similar to c-type lysozymes ( Chiu et al, 2004 ; Wagner et al, 2015 ). Afterwards, it has been reported that the protein could be a target for anti-sperm antibodies in some infertile male, playing possible roles in sperm-egg bonding process, as well as subsequent development of early embryo in hamster, murine or bovine models ( Prendergast et al, 2014 ). In this study, the expression of SPRASA was higher in cryopreserved goat spermatozoa without antioxidant cryo-protection, suggesting that this protein may be a potential infertile marker of frozen-thawed goat sperm, and its specific molecular function is worth further exploration.…”
Section: Discussionmentioning
confidence: 99%